Implementation of Loose Part Play STEM (Science, Technology, Engineering, and Mathematics) Media on STEM Understanding of Pre-service Teachers: A Case Study in Serang City, Indonesia - Reza Febri Abadi; Siti Musayaroh; Sistriadini Alamsyah Sidik; Neti Asmiati; Toni Yudha Pratama; Dedi Mulia; Yuni Tanjung Utami; Sayidatul Maslahah (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This study aimed to implement the STEM (Science, Technology, Engineering, and Mathematics)-based Loose Part Play Media on an understanding of cerebral palsy pre-service teachers in the city of Serang. The participants in this study are cerebral palsy pre-service teachers in Serang, Indonesia. The participant was 21 teachers. The method in this activity is a case study. The results showed that increasing of the STEM understanding was 26.2. It can be concluded that the STEM-based loose part play media can increase the STEM understanding of the pre-service teachers to find solutions to the problems faced by cerebral palsy pre-service teachers in Serang. An increase in understanding achievement indicates this through loose part play STEM of 26.2 (seen from the initial and final test), and the pre-service teacher's understanding of STEM-based loose play part media is 82.5.